Implementasi Metrik Keluaran Unjuk Kerja Network Intrusion Detection System - Yudhi Ardiyanto (Universitas Muhammadiyah Yogyakarta, 2016)
Perfomance of Network Intrusion Detection System (NIDS) very important to be monitored, because this system must perform packet inspection on computer network. Failure to detect data packets can produce malicious packet sneak into networks. Snort is one of the NIDS plug ins in the form of perfomance statistics that will provide performance information in real time, in the form of comma delimited value format. It takes long time to generated performance information. Thepigdoktah is a tools that can be used to process the output performance of the NIDS to be more informative .This research has been successfully implemented on a computer network, one of the performance information that can be generated is the average packet loss amounted to 0,012%.